SIMPLIFYING HYBRID CLOUD ADOPTION WITH AWS realize edge computing and build compelling hybrid solutions on premises with AWS Outposts - Negro, Frankie Costa (PACKT PUBLISHING LIMITED, 2022)
Become an expert in AWS Outposts and Hybrid architectures with in-depth explanations of the product and order processes while exploring the capabilities for creating next-generation edge solutions Key Features Learn AWS Outposts from the ground up guided by an AWS hybrid edge solutions architect Master hybrid edge concepts, use cases, and architectures and discover how AWS Outposts fits into this space Become the go-to professional for designing, deploying, operating, and maintaining AWS Outposts Book Description The hybrid edge specialty is often misunderstood because it began with an on-premises-focused view encompassing everything not running inside the traditional data center. If you too have workloads that need to live on premises and need a solution to bridge the gap between both worlds, this book will show you how AWS Outposts allows workloads to leverage the benefits of the cloud running on top of AWS technology. In this book, you'll learn what the Edge space is, the capabilities to look for when selecting a solution to operate in this realm, and how AWS Outposts delivers. The use cases for Outposts are thoroughly explained and the physical characteristics are detailed alongside the service logical constructs and facility requirements. You'll gain a comprehensive understanding of the sales process--from order placement to rack delivery to your location. As you advance, you'll explore how AWS Outposts works in real life with step-by-step examples using AWS CLI and AWS Console before concluding your journey with an extensive overview of security and business continuity for maximizing the value delivered by the product. By the end of this book, you'll be able to create compelling hybrid architectures, solve complex use cases for hybrid scenarios, and get ready for your way forward with the help of expert guidance. What you will learn Discover the role of AWS Outposts in the hybrid edge space Understand rack components with typical use cases for AWS Outposts Explore AWS services running on Outposts and its capabilities Select, order, and successfully deploy your Outposts Work with Outposts resources for hands-on operations Assess logical and physical security aspects and considerations Monitor and log configuration and usage to improve your architecture Maintain and troubleshoot hardware and software that run AWS services Who this book is for If you are a seasoned data center professional, this book will empower you to support businesses to build hybrid edge solutions with AWS technology. It will also help AWS Cloud professionals to master a unique offering in the AWS portfolio that takes Amazon web services beyond the regions. Familiarity with AWS services and traditional data center concepts is assumed.